Pengembangan Buku Ajar Berbasis Multimedia pada Pembelajaran Qawā’id di Tingkat Madrasah Aliyah - Pratiwi, A. Ayu; Herdah, Herdah; Kaharuddin, Kaharuddin; Darmawati, Darmawati; Hamsa, Hamsa (Shaut al Arabiyyah, 2024)
This study discusses the development of multimedia-based textbooks for Qawā'id learning at the Madrasah Aliyah level. The formulation of the problems in this study are: 1) Describing the prototype for the development of multimedia-based textbooks on qawaid learning at the Islamic Senior High School. 2) Testing both the validity and practicality of multimedia-based textbooks on qawaid learning at the Islamic Senior High School. 3) Describing the effectiveness of multimedia-based textbooks on qawaid learning at the Islamic Senior High School. The type of research used is Research and Development, which refers to Sugiyono's model (Potentials and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trials, Product Revisions, Usage Trials, Product Revisions and Mass Products). Multimedia-based textbook was developed through the Kind Master application downloaded from the Google Play Store. The developed media was tested for feasibility by media expert validators and material experts and practitioners by educators, as well as a feasibility test based on 30 students’ responses of class XI at YMPI Rappang Madrasah Aliyah. The results of this study were 1) A multimedia-based textbooks supplemented with videos 2) the multimedia-based textbooks were proved valid with the material expert validation result reached 94.11%, media expert validation result reached 92% and learning expert validation result reached 96.66%, the result of small class trials reached 95% and large class trials reached 94.5% 3). This book was declared effective by calculating the pretest score of 59.10, and the posttest score was 86.23. 86.23 minus 59.10 equals 27.133. It meant that there was a difference of 27.133. Based on this result, it was known that the sig (2-tailed) value is 0.000 <0.05. Because of the sig.(2-tailed) value is 0.000 less than 0.05, so there was an increase in learning outcomes with the use of the multimedia-based textbooks, it was concluded that Ha was accepted and Ho was rejected which meant that the multimedia-based textbooks were effectively used in qawā'id learning at the Islamic Senior High School.